Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1007/s12192-019-01029-4
|View full text |Cite
|
Sign up to set email alerts
|

Co-enzyme Q10 protects primary chicken myocardial cells from heat stress by upregulating autophagy and suppressing the PI3K/AKT/mTOR pathway

Abstract: In this study, we investigated the function of co-enzyme Q10 (Q10) in autophagy of primary chicken myocardial cells during heat stress. Cells were treated with Q10 (1 μΜ, 10 μΜ, and 20 μM) before exposure to heat stress. Pretreatment of chicken myocardial cells with Q10 suppressed the decline in cell viability during heat stress and suppressed the increase in apoptosis during heat stress. Treatment with 20 μM Q10 upregulated autophagy-associated genes during heat stress. The expression of LC3-II was highest in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…In examining the Author keywords, some underdeveloped and marginally important topics grouped into the emerging and declining themes were “hsp70”, “rna-seq”, “co-enzyme q10”, and “transcriptome”. To address this, studies have reported that co-enzyme q10 protects the chicken primary myocardial cells against damage and apoptosis during in vivo heat stress by upregulating hsp70 expression and HSF1 binding activity ( Xu et al, 2017a ; Xu et al, 2017b ; Xu et al, 2019b ), and that co-enzyme q10 induced autophagy and suppressed the PI3K/AKT/mTOR signaling as a protective mechanism against heat stress ( Xu et al, 2019a ). Alongside this, several studies have employed the whole transcriptomics approach, as well as other RNA sequencing technology to investigate the effects of heat stress in poultry ( Saelao et al, 2018 ; Te Pas et al, 2019 ; Kim et al, 2021 ; Liang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In examining the Author keywords, some underdeveloped and marginally important topics grouped into the emerging and declining themes were “hsp70”, “rna-seq”, “co-enzyme q10”, and “transcriptome”. To address this, studies have reported that co-enzyme q10 protects the chicken primary myocardial cells against damage and apoptosis during in vivo heat stress by upregulating hsp70 expression and HSF1 binding activity ( Xu et al, 2017a ; Xu et al, 2017b ; Xu et al, 2019b ), and that co-enzyme q10 induced autophagy and suppressed the PI3K/AKT/mTOR signaling as a protective mechanism against heat stress ( Xu et al, 2019a ). Alongside this, several studies have employed the whole transcriptomics approach, as well as other RNA sequencing technology to investigate the effects of heat stress in poultry ( Saelao et al, 2018 ; Te Pas et al, 2019 ; Kim et al, 2021 ; Liang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are limited reports regarding the effects of Vit E/Se combination on mTOR activity in broilers. More recently, CoQ10 treatment significantly upregulated autophagy and suppressed the PI3K/Akt/mTOR pathway to protect primary chicken myocardial cells exposed to HS ( Xu et al., 2019 ). Similarly, decrease in mTOR mRNA abundance was also reported in HS broilers fed Noni- (a plant source rich in a variety of phytochemicals and antioxidants) supplemented diets ( Rajaei-Sharifabadi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, Zhang et al [ 116 ] experimentally confirmed the ability of CoQ10 to induce mitophagy via the PINK1 (PTEN-induced kinase 1)-Parkin pathway in the stressed cells of a mouse with acetaminophen-induced liver injury. In addition, CoQ10 has been found to protect chicken myocardial cells during heat stress through deactivation of the PI3K/Akt/mTOR pathway and upregulation of autophagy-associated genes [ 117 ]. Supplementation of rats with acute myocardial ischemia-reperfusion injury with CoQ10 has been found to induce the autophagy [ 118 ].…”
Section: Modulation Of Autophagy By Nutraceuticals: Support For the T...mentioning
confidence: 99%